Assessment of the Hydromorphological State of the Irpin Basin Rivers After the Influence of Military Actions - Ivanova, N. O.; Dubniak, S. S.; Nezbrytska, I. M.; Lietytska, O. M.; Pohorielova, M. S.; Prychepa, M. V.; Zorina-Sakharova, K. Ye.; Afanasyev, S. O. (Ukrainian Geographical Journal, 2024)
The study aimed to conduct a hydromorphological assessment of the main types of surface water bodies (SWB) in the Irpin River basin and to determine the degree of change in the hydromorphological characteristics of water bodies in the areas affected by the war. The assessment was carried out based on the analysis of the results of expeditionary research in 2023–2024 using stock, literary, cartographic data, and space photographs according to the “Methodology of hydromorphological monitoring of surface water bodies of the categories ‘Rivers’ and ‘Lake’ adopted in Ukraine” (2019) and from considering the practice of conducting similar studies on other river basins in Ukraine and the EU. It was established that the studied areas belong to the I–IV class of hydromorphological condition; in particular, the II–III class prevails on small rivers, both I–II and IV classes are observed on medium ones, and large ones (the Irpin River in the lower and middle reaches) I–IV class with a slight predominance of II class. The main factors affecting the deterioration of the hydromorphological state are the regulation of flow by ponds and reservoirs, morphological changes in the riverbed and coastal zone, reclamation of hydrotechnical structures, and using floodplains for economic needs. Hydromorphological indicators before and after the impact of military operations were determined to assess the degree of impact of military operations. Changes in the HM condition were established in the destruction and subsequent restoration of bridges and hydraulic structures. The estuary of the Irpin River, where the HM class changed from II to IV, suffered the greatest military impact. Based on cluster analysis, groups of sites with similar hydromorphological conditions and the degree of military influence were selected. Differences in the HM condition in the main morphological zones of rivers—riverbed, coastal zone, and floodplain were evaluated.
Keywords: hydromorphological assessment; river basin; Irpin; surface water bodies; survey area; impact of military operations